Analisis Kesesuaian Lahan Untuk Pengembangan Perumahan dan Kawasan Permukiman di Kecamatan Talawaan Kabupaten Minahasa Utara - Farrel Lambris; Reny Syafriny; Ricky Lakat (Universitas Sam Ratulangi, 2021)
Land suitability is a measurement of a certain land use whether it is in accordance with the land capability in terms of land cover ratio directions, building height directions, raw water utilization directions, and land capacity. This research was conducted in Talawaan Subdistrict, North Minahasa Regency to determine the spatial capacity and suitability of the land carrying capacity in Talawaan Subdistrict for the development of large-scale new settlement functions based on the Regional Regulation of North Minahasa Regency Number 1 of 2013 about Regional Spatial Planning for North Minahasa Regency 2013- 2033. The method used is descriptive analysis method and overlay of various basic physical maps, such as maps of morphology, topography, geology, soil types, hydrology, rainfall, land use, natural disasters, and land capability unit maps obtained later. The results of this study indicated that the land in Talawaan District is feasible to develop for new residential functions on a massive scale by taking into account the applicable technical terms and conditions.Â Keyword: Land Capability, Land Suitability, Talawaan Subdistrict.